2019
DOI: 10.12688/wellcomeopenres.15100.1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of using primaquine without prior G6PD testing: a case series describing the obstacles to the medical management of haemolysis

Abstract: Radical cure of malaria in glucose-6-phosphate Plasmodium vivax dehydrogenase (G6PD) deficient individuals employs weekly primaquine dosing. This is the only recommended regimen for this patient sub-group. If national malaria programs mandate daily primaquine dosing (the recommended regimen for G6PD normal individuals), then G6PD testing before prescription is necessary to avoid iatrogenic haemolysis in G6PD deficient individuals. In this case series, two infected patients with P. vivax unknown G6PD status fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…In two of the cases reported here (Cases 1 and 4), the haemolytic crisis did not halt with the cessation of dosing but continued for the 2–3 days leading up to hospitalization and transfusion. This has been observed by others [ 29 , 30 , 31 ]. In the instance of Case 5, the crisis progressed so rapidly that transfusion occurred on the same day of PQ cessation ( Figure 2 ).…”
Section: Discussionsupporting
confidence: 83%
“…In two of the cases reported here (Cases 1 and 4), the haemolytic crisis did not halt with the cessation of dosing but continued for the 2–3 days leading up to hospitalization and transfusion. This has been observed by others [ 29 , 30 , 31 ]. In the instance of Case 5, the crisis progressed so rapidly that transfusion occurred on the same day of PQ cessation ( Figure 2 ).…”
Section: Discussionsupporting
confidence: 83%
“…P. knowlesi patients were given treatment with primaquine, which is a radical cure to clear hypnozoites (dormant liver stage) of P. vivax . This resulted in unnecessary increase of treatment cost and potential health risks to individuals with glucose-6-phosphate dehydrogenase (G6PD) deficiency if G6PD testing was not performed prior to the treatment, which could lead to severe acute haemolytic anaemia [ 94 ]. Therefore, differential diagnosis is essential in distinguishing knowlesi malaria from malaria caused by other species of Plasmodium , by taking into considerations the parasite’s morphology and patient’s travel history prior to the infection.…”
Section: Introductionmentioning
confidence: 99%
“…In erythrocytes with the G6PD Mahidol 487A mutation, oxidation of membrane proteins causes the cells to rigid, nondeformable, and finally haemolysis. A recent report has indicated that patients with G6PD Mahidol G487A presented symptoms of acute haemolytic anaemia after taking an incorrect dose of PQ [ 44 ]. Although this study had no haematological data to support the clinical impact of anti-malarial drugs on patients with G6PD Mahidol G487A and other mutations, these findings provided evidence for malaria infection-induced haemolysis in patients with G6PD deficiency.…”
Section: Discussionmentioning
confidence: 99%